2018
DOI: 10.1016/j.ibmb.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The Manduca sexta serpinome: Analysis of serpin genes and proteins in the tobacco hornworm

Abstract: Members of the serpin superfamily of proteins occur in animals, plants, bacteria, archaea and some viruses. They adopt a variety of physiological functions, including regulation of immune system, modulation of apoptosis, hormone transport and acting as storage proteins. Most members of the serpin family are inhibitors of serine proteinases. In this study, we searched the genome of Manduca sexta and identified 32 serpin genes. We analyzed the structure of these genes and the sequences of their encoded proteins.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 86 publications
1
29
0
Order By: Relevance
“…We have shown that HP5 cleaves proHP6 after a His residue, a very unusual protease specificity. None of the M. sexta serpins has a His residue at the predicted P1 residue of the scissile bond of reactive center loop that determines primary selectivity of serpins in protease inhibition (30). Serpin-4 has an Arg residue at the P1 site (31).…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that HP5 cleaves proHP6 after a His residue, a very unusual protease specificity. None of the M. sexta serpins has a His residue at the predicted P1 residue of the scissile bond of reactive center loop that determines primary selectivity of serpins in protease inhibition (30). Serpin-4 has an Arg residue at the P1 site (31).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we found that full length serpin-3 expressed in E. coli was not fully active 13 . Therefore, we produced a new construct with deletion of the amino-terminal 30 residues of serpin-3, not present in most other serpins 11 and found in preliminary experiments that this construct, serpin-3ΔN, retained inhibitory activity. The serpin-3ΔN sequence encoding 31-435 residues of the mature protein was amplified from full-length serpin-3 in vector H6pQE60 13 by PCR, using a forward primer.…”
Section: Expression and Purification Of Pap3 And Serpin-3∆n Recombinmentioning
confidence: 99%
“…Immune responses mediated by hemolymph serine proteases and their regulation by serpins have been studied intensively in a model species, Manduca sexta , the tobacco hornworm 10 . The M. sexta genome contains 32 serpin genes, and only 10 of these have been studied with regard to their function 11 , 12 . M. sexta serpin-3 expression increases during immune challenge, and it inhibits key proteases in two immune cascades.…”
Section: Introductionmentioning
confidence: 99%
“…The number of serpin genes documented in insects seems to be dominated by lepidopteron insects as compared to other insect orders. For instance, in B. mori , 34 serpin genes have been reported (Zou, Picheng, Weng, Mita, & Jiang, ) followed by 32 in M. sexta (M. Li et al, ). Though dipteran insects contain a fair number of serpin genes, however, the number varies from 31 reported in Culex quinquefasciatus to 18 in Anopheles gambiae (Gulley et al, ).…”
Section: Serpins In Insects and Their Role In Host‐pathogen Interactionmentioning
confidence: 99%